2014
DOI: 10.1007/s12206-014-1036-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of silicon nanoparticle formation in inductively coupled plasma using a modified collision frequency function

Abstract: A model is presented to describe particle growth in inductively coupled plasma. The model consists of plasma chemistry and a coagulation module that adopts a modified collision frequency function. The modified collision frequency function is modified by a collision correlation factor that reflects the repulsive force of the particle charge in plasma in order to describe the reduction of coagulation among medium size particles (around 100 nm). In this model, plasma state and concentration of nuclei are determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In addition, in order to explain a high cluster growth rate observed experimentally, Mankelevich et al [36] considered an additional attraction between the particles and introduced a polarizationinduced ion flow asymmetry mechanism to the dust particle coagula tion. Subsequently, Kim et al [37], using a modified collision frequency function between the nanoparticles in a coagulation module, investigated particle growth in an inductively coupled plasma. De Bleecker et al [38,39], by a 1D fluid model cou pling with an aerosol dynamics model, in which the charging of particles was taken into account based on orbitalmotion limited (OML) probe theory [40], showed that large particles during the dust growth tend to accumulate near the sheath region with their density distribution like a bimodal struc ture, while small particles are inclined to stay in the discharge bulk.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in order to explain a high cluster growth rate observed experimentally, Mankelevich et al [36] considered an additional attraction between the particles and introduced a polarizationinduced ion flow asymmetry mechanism to the dust particle coagula tion. Subsequently, Kim et al [37], using a modified collision frequency function between the nanoparticles in a coagulation module, investigated particle growth in an inductively coupled plasma. De Bleecker et al [38,39], by a 1D fluid model cou pling with an aerosol dynamics model, in which the charging of particles was taken into account based on orbitalmotion limited (OML) probe theory [40], showed that large particles during the dust growth tend to accumulate near the sheath region with their density distribution like a bimodal struc ture, while small particles are inclined to stay in the discharge bulk.…”
Section: Introductionmentioning
confidence: 99%